The Limits of Rehabilitation and Recidivism Reduction: Rethinking the Evaluation of Arts Programming in Prisons - Van der Meulen, Emily (The prison journal, 2021)
Canadian prison-based arts and other programming are limited at best. Even the country’s Correctional Investigator, or prison-ombudsperson, has critiqued the lack of meaningful options in which prisoners can engage. Those programs that do exist tend to be focused on the logic of penal rehabilitation, with the end goal of reducing recidivism. In this article, we showcase the evaluation of a 9-week arts program in a women’s prison, the aim of which was to build community and foster artistic engagement, thus running counter to normative carceral logics.